The prognostic value and pathophysiologic significance of three‐dimensional fluid‐attenuated inversion recovery (3D‐FLAIR) magnetic resonance imaging in idiopathic sudden sensorineural hearing loss: A systematic review and meta‐analysis. (2nd October 2019) - Lammers, Marc J. W.; Young, Emily; Fenton, David; Lea, Jane; Westerberg, Brian D.
Abstract: Background: The underlying pathophysiology of idiopathic sudden sensorineural hearing loss (ISSNHL) is still unknown. However, an increasing number of observational studies report intralabyrinthine signal alterations in patients with ISSNHL using three‐dimensional fluid‐attenuated inversion recovery (3D‐FLAIR) magnetic resonance imaging (MRI). These findings warrant a meta‐analysis. Objective of review: To conduct a meta‐analysis assessing the value of 3D‐FLAIR MRI in identifying possible underlying labyrinthine pathophysiologic mechanisms and prognostication in patients with ISSNHL. Search strategy: Two reviewers independently searched the Pubmed, Embase and Cochrane Library from inception until October 10, 2018 and evaluated eligibility based on titles and abstracts of all retrieved studies. All studies reporting on 3D‐FLAIR imaging in ISSNHL were included. Subsequently, the full text of eligible studies were evaluated. Evaluation method: Adhering to the MOOSE guideline, two independent reviewers extracted data, assessed risk of bias and evaluated the relevance and quality of evidence. Data on the number of patients and events were extracted and hearing levels were converted to standardised mean differences (SMD) for conducting meta‐analyses. Random effects models for meta‐analyses were applied. Results: Eight observational studies met our inclusion criteria (n = 638 patients). In 29%, high signal intensity was found on 3D‐FLAIR imaging, suggesting labyrinthine pathology (labyrinthitis [79%], intralabyrinthine haemorrhage [21%]). High signal intensity on 3D‐FLAIR was associated with poorer hearing (SMD: 14 dB, 95% CI 5.67‐22.94) and vertigo (RR: 1.92, 95% CI 1.16‐3.17) at baseline. Multivariate analyses demonstrated that patients with high 3D‐FLAIR signal intensity had 21 dB lower final hearing pure‐tone averages (SMD: 21 dB, 95% CI 9.08‐33.24). Conclusions: Three‐dimensional fluid‐attenuated inversion recovery MR imaging can identify an underlying labyrinthine condition in up to 29% of patients with sudden hearing loss in whom previously no cause could be identified. Their final pure‐tone averages are more than 20 dB worse than 3D‐FLAIR–negative patients, suggesting more severe labyrinthine damage. Findings such as these may contribute to our understanding of pathophysiologic mechanisms of ISSNHL.